HAEMATOLOGICAL VARIATIONS ASSOCIATED WITH ALCOHOL CONSUMPTION IN A NIGERIAN UNIVERSITY COMMUNITY - Etura, Joyce; Andrew, Kisamhar; Akpan, Uwem; Jeremiah, Zaccheaus (Sanamed, 2024)
Introduction: Alcohol consumption is widespread, contributing to approximately 3 million deaths worldwide. This study aimed to assess haematological indices among alcohol consumers compared to non-consumers in the University of Calabar Community, Nigeria.Materials and Methods: This case-control study enrolled 100 subjects (50 alcohol consumers and 50 non-consumers) from the University of Calabar community. Blood samples were collected aseptically for Full Blood Count and Thrombin Time analysis. Rigorous study design, meticulous data collection, and thorough analysis ensured the reliability of our findings.Results: The mean corpuscular volume (MCV)(76.21±7.35 fl), mean corpuscular haemoglobin (MCH)(25.31±3.26 pg), Platelet (PLT)(154.38±54.89 x 109) and Platelet Crit (PCT)(0.14±0.04%) of alcohol consumers were significantly lower than that of the controls respectively (79.36±5.76 fl, 26.47± 2.15 pg, 187.22± 58.34 x 109and 0.17±0.04%)(p0.05) between the two groups of subjects studied. A significant negative correlation (r=0.801, p=0.001) was observed between Thrombin time and Plateletcrit in the test subjects. In contrast, a significant positive correlation (r=0.698, p=0.001) was observed between Mean Corpuscular Haemoglobin Concentration and Haemoglobin in alcohol consumption. A significant negative correlation (r=0.973, p=0.001) was observed between lymphocytes and granulocytes in percentage in the test subjects. These significant findings provide valuable insights into the haematological variations associated with alcohol consumption.Conclusion: These significant differences observed in this study underscore the impact of alcohol consumption on haematological indices. The study concluded that derangements in some hematological parameters occur in alcoholics, which can affect their quality of life.
Keywords: Haematology; Alcohol consumers; Platelet count